Using Environmental Marketing Tools in the Implementation of the Concept of Sustainable Development of the Region - Bolotina, Y.; Shubna, O.; Nykolaiva, Y. (Економічний вісник Донбасу, 2019)
The article describes the development of the concept of ecological marketing in the region. It has been determined that in the existing ecological, social and economic conditions, the main tasks of ecological marketing in the region include the tasks of forming and developing the environmental goods market in order to resolve differences between economic development and the need to preserve and further improve environmental quality. A mechanism for calculating the price of environmental goods. It is determined that the main elements of communications in the system of environmental marketing is advertising, sales promotion, public relations and personal selling. Communication activities help build trust with producers and their products, help explain the content and meaning of ecolabeling, which is an advertising medium and can serve as a guide for consumers when choosing products and increasing the competitiveness of products. У статті розглянуто розвиток концепції екологічного маркетингу регіону. Визначено, що в існуючих еколого-соціально-економічних умовах до головних завдань екологічного маркетингу регіону відносять завдання формування і розвитку ринку екологічних товарів з метою розв'язання суперечностей між економічним розвитком і необхідністю збереження і подальшого поліпшення якості довкілля. Розроблено механізм розрахунку ціни екологічного товару. Визначено, що основними елементами комунікацій в системі екологічного маркетингу є реклама, стимулювання збуту, зв’язки з громадськістю та персональний продаж. Комунікаційні заходи допомагають сформувати довірчі відносини до виробників та їх продукції, допомагають пояснити зміст і значення екологічного маркування, яке є рекламним засобом і може слугувати орієнтиром для споживачів при виборі продукції та підвищувати конкурентоспроможність товарів. В статье рассмотрено развитие концепции экологического маркетинга региона. Определено, что в существующих эколого-социально-экономических условиях к главным задачам экологического маркетинга региона относят задачи формирования и развития рынка экологических товаров с целью решения разногласий между экономическим развитием и необходимостью сохранения и дальнейшего улучшения качества окружающей среды. Разработан механизм расчета цены экологического товара. Определено, что основными элементами коммуникаций в системе экологического маркетинга является реклама, стимулирование сбыта, связи с общественностью и персональная продажа. Коммуникационные мероприятия помогают сформировать доверительные отношения к производителям и их продукции, помогают объяснить содержание и значение экологического маркирования, которое является рекламным средством и может служить ориентиром для потребителей при выборе продукции и повышать конкурентоспособность товаров.